Skrining Fitokimia dan Uji Antibakteri Ekstrak Rimpang Lengkuas Putih (Alpinia Galanga L.) terhadap Bakteri Klebsiella Pneumoniae di Laboratorium Sekolah Tinggi Ilmu Kesehatan Santa Elisabeth Medan - Nela Bohalima; Seri Rayani Bangun; Rica Vera Br Tarigan; David Sumanto Napitupulu (Universitas Malahayati Lampung, 2025)
ABSTRACT White galangal rhizome (Alpinia galanga L.) is a plant known to contain secondary metabolite compounds with potential antibacterial properties. Klebsiella pneumoniae is a Gram-negative bacterium that causes pneumonia, a serious lung infection that remains one of the most common infectious diseases despite a decline in its incidence rate. This study aimed to identify the secondary metabolite compounds present in white galangal rhizome extract and evaluate its antibacterial activity against the growth of Klebsiella pneumoniae. The research was conducted using an experimental method with a post-test only control group design. Phytochemical screening revealed that the extract contains flavonoids, alkaloids, saponins, phenols, and terpenoids. The antibacterial test was carried out using the Kirby-Bauer disk diffusion method. The inhibition zones observed at concentrations of 20%, 40%, and 60% were 2 mm (weak), 11.8 mm (moderate), and 14.7 mm (strong), respectively. Statistical analysis using One Way ANOVA yielded significant results (p 0.05), indicating that the extract had an inhibitory effect on bacterial growth. The findings demonstrate that the white galangal rhizome extract is effective in inhibiting the growth of Klebsiella pneumoniae, particularly at higher concentrations. The presence of active secondary metabolites supports its potential use as a natural antibacterial agent. This study suggests that white galangal rhizome could be developed further as an alternative treatment for bacterial infections caused by Klebsiella pneumoniae. Keywords: White Galangal, Klebsiella Pneumoniae, Antibacterial Test, Hytochemical Screening. ABSTRAK Rimpang lengkuas putih (Alpinia galanga L.) merupakan tanaman yang mengandung senyawa metabolit sekunder dan berpotensi sebagai antibakteri. Klebsiella pneumoniae adalah bakteri Gram negatif penyebab pneumonia, yaitu infeksi paru-paru yang masih memiliki angka kejadian tinggi meskipun menurun setiap tahunnya. Penelitian ini bertujuan untuk mengetahui kandungan senyawa metabolit sekunder serta aktivitas antibakteri ekstrak rimpang lengkuas putih terhadap pertumbuhan Klebsiella pneumoniae. Uji dilakukan menggunakan metode Eksperimen dengan desain post test only control group. Hasil skrining fitokimia menunjukkan bahwa ekstrak mengandung flavonoid, alkaloid, saponin, fenol, dan terpenoid. Daya hambat yang dihasilkan terhadap Klebsiella pneumoniae menunjukkan peningkatan seiring peningkatan konsentrasi: 20% sebesar 2 mm (daya hambat lemah), 40% sebesar 11,8 mm (sedang), dan 60% sebesar 14,7 mm (kuat). Hasil uji statistik menggunakan One Way ANOVA menunjukkan nilai signifikan (p 0,05), yang berarti terdapat daya hambat ekstrak terhadap pertumbuhan bakteri. Dengan demikian, ekstrak rimpang lengkuas putih terbukti memiliki senyawa aktif yang berperan dalam aktivitas antibakteri dan mampu menghambat pertumbuhan Klebsiella pneumoniae secara signifikan, terutama pada konsentrasi tinggi. Penelitian ini mendukung potensi rimpang lengkuas putih sebagai agen antibakteri alami. Kata Kunci: Rimpang Lengkuas Putih, Klebsiella Pneumoniae, Uji Antibakteri, Skrining Fitokimia